THE COMPARATIVE STUDY OF THE NOVEL AND THE FILM OF HARRY POTTER “THE DEATHLY HALLOWS” - Maranaek Pemberian Silaban; nopriansah nopriansah (UNIVED Press, 2018)
This study aimed to describe the defamiliarization in Paulo Coelho’s novel entitled “The Alchemist”. Lack of textual study and formalism use was become the common problem why this thesis were made. Formalism believe that meaning itself contained in form of text. Therefore, the author of this research take “A Defamiliarization of the Alchemist by Paulo Coelho” as the title. The purpose of this study were: (1) to know the use of defamiliarization, (2) to understand the meaning of defamiliarization in this novel. A qualitative descriptive method was adopted to conduct this study. Several data that has been gathered were archived. Using domain to recognize the data classify, then taxonomy to find the most frequent data and componential were used to make the conclusion. After separating and classify the word, the author uses Viktor defamiliarization to find the strange and interpret the meaning. Defamiliarization was used in Coelho’s novel and meaning that separated into two forms, connotative and denotative. As the conclusion, the researcher found that defamiliarization used to deceive the reader and perceive the reader from the common words or sentence or meaning. The most frequent data of the defamiliarization was strange and the most frequent meaning used were connotative. Keywords: Defamiliarization, Formalism, Meaning, Text, the Alchemist.